Back Cover Image. Issue 12 (4th December 2022) - Bhat, Gurudutt; Kielar, Marcin; Rao, Haixia; Gholami, Mahnaz D.; Mathers, Isabel; Larin, Astrid C. R.; Flanagan, Thomas; Erdenebileg, Enkhtur; Bruno, Annalisa; Pannu, Amandeep Singh; Fairfull‐Smith, Kathryn E.; Izake, Emad L.; et al.
Abstract: This cover (DOI: 10.1002/inf2.12345 ) shows a multifunctional TPA‐azaBODIPY‐TPA small molecule with superior optoelectronic and photophysical properties. Material is shown to function as an efficient hole transport layer in perovskite solar cells reaching a power conversion efficiency of 17.4%, and as a robust electron donor in near‐infrared organic photodetectors absorbing light in the wavelength range of up to 800 nm. Offering two distinct optoelectronic functions, TPA‐azaBODIPY‐TPA is particularly attractive as it enables multi‐purpose applications while maintaining the ease of fabrication. Abstract : This cover (DOI: 10.1002/inf2.12345 ) shows a multifunctional TPA‐azaBODIPY‐TPA small molecule with superior optoelectronic and photophysical properties. Material is shown to function as an efficient hole transport layer in perovskite solar cells reaching a power conversion efficiency of 17.4%, and as a robust electron donor in near‐infrared organic photodetectors absorbing light in the wavelength range of up to 800 nm. Offering two distinct optoelectronic functions, TPA‐azaBODIPY‐TPA is particularly attractive as it enables multi‐purpose applications while maintaining the ease of fabrication.